1997
DOI: 10.1038/ng0397-247
|View full text |Cite
|
Sign up to set email alerts
|

Kerato-epithelin mutations in four 5q31-linked corneal dystrophies

Abstract: Granular dystrophy Groenouw type I (CDGG1), Reis-Bücklers (CDRB), lattice type I (CDL1) and Avellino (ACD) are four 5q31-linked human autosomal dominant corneal dystrophies. Clinically, they show progressive opacification of the cornea leading to severe visual handicap. The nature of the deposits remains unknown in spite of amyloid aetiology ascribed to the last two. We generated a YAC contig of the linked region and, following cDNA selection, recovered the beta ig-h3 gene. In six affected families we identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
238
1
7

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 450 publications
(254 citation statements)
references
References 25 publications
8
238
1
7
Order By: Relevance
“…All affected members of the family have an R124C mutation in the BIGH3 gene. The same mutation was found in Caucasian 3 and Japanese patients with LCDI. 24 This suggests that this mutation occurs independently in several ethnic groups.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…All affected members of the family have an R124C mutation in the BIGH3 gene. The same mutation was found in Caucasian 3 and Japanese patients with LCDI. 24 This suggests that this mutation occurs independently in several ethnic groups.…”
Section: Discussionsupporting
confidence: 70%
“…This mutation has previously been reported in LCDI. [3][4][5][6] The unaffected members of the family did not have the mutation as determined by a cosegregation study of the restriction digest analysis in which the mutation abolishes the recognition site of AvaII. The three affected members showed one undigested product of the expected size (310 bp) for the mutant allele plus two restriction digest products (190 bp and 110 bp) from the normal allele.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Recent molecular analysis showed that different types of corneal dystrophies are caused by mutations in the transforming growth factor beta-induced gene (TGFBI), located on chromosome 5q31. [2][3][4] Several phenotypes are caused by specific mutations in the TGFBI gene such as: lattice corneal dystrophy type I (CDL1, OMIM122200), lattice corneal dystrophy type IIIA (LCDIIIA), granular corneal dystrophy (CDGG1, OMIM 121900), Avellino corneal dystrophy (ACD, OMIM 121900), Reis-Bü cklers's corneal dystrophy (CDRB, OMIM 121900), and Thiel-Behnke corneal dystrophy (CDB2, OMIM 602082). 1,4,5 Keratoepithelin, the protein product of the TGFBI gene, is an extracellular matrix protein expressed in many tissues including corneal epithelium.…”
Section: Introductionmentioning
confidence: 99%